SOSIALISASI PENGELOLAAN ARSIP PADA KANTOR BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI TENGAH - Nurapiah Nurapiah; akhmad akhmad (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2022)
This activity aims to provide an overview of the role of archives for leaders in decision making at the Office of the Regional Personnel Agency of Central Sulawesi Province. The problem regarding the role of archives is very important in an organization considering that archives as a result of every administrative activity are stored and can be reused if needed both as material for accountability, authentic evidence, as a memory center and as information material in every decision making. The research was conducted by analyzing qualitatively to obtain descriptions of the role of archives for leaders in making decisions as expected. The results of the study indicate that the organization's functions are still less than optimal so that it has an impact on organizational goals that have not yet achieved maximum results.